Model Partisipasi Penta Helix dalam Penanganan Stunting di Kota Depok: Hambatan, Strategi, dan Tantangan Penguatan Kesejahteraan Sosial - Karno; Ahmad Averus Toana; Mulyadi; Hyronimus Rowa (JOM, 2024)
Stunting remains a national health priority issue, including in the Depok City Government with a prevalence of 19.8% of toddlers experiencing chronic malnutrition. In addition, low community participation, although intervention programs have been carried out by the government. The purpose of this study was to examine the level of community participation, identify obstacles, and formulate strategies to increase participation in handling stunting. The method used in this study was descriptive qualitative, data collection through in-depth interviews with Posyandu cadres, mothers of toddlers, and health workers, and document analysis. Data processing was carried out thematically using QDA Miner 6.0 software. The results showed that community participation was mostly symbolic, and at the informing and consulting level with the main contribution being attendance at Posyandu activities and basic education and limited involvement in decision-making. The main obstacles include minimal education, less than optimal cross-sector coordination, and limited access to health services and technology. The proposed strategies include technology-based education, ongoing cadre training, local community empowerment, and strengthening cross-sector collaboration. The main finding of this study is a participation model based on the penta helix approach, involving the government, community, private sector, academics, and media, to improve the effectiveness of stunting management in a sustainable manner. The findings of the model are expected to be the basis for developing public health policies based on inclusive participation in improving social welfare.